VD_FINDINFO Pron / 2013 / 250 vom 23. September 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, RADIATION DU RÔLE, ASSISTANCE JUDICIAIRE, DÉCISION SUR FRAIS | 109 al. 1 CPC (CH), 117 CPC (CH), 122 CPC (CH), 123 CPC (CH), 241 CPC (CH)